Uncertainty Reasoning for the Semantic Web - Lukasiewicz, T (Springer, 2009)
Significant research activities have recently been directed towards the Semantic Web as a potential future substitute of the current World Wide Web. Many experts predict that the next huge step forward in Web information technology will be achieved by adding semantics to Web data. An important role in research towards the Semantic Web is played by formalisms and technologies for handling uncertainty and/or vagueness. In this paper, I first provide some motivating examples for handling uncertainty and/or vagueness in the Semantic Web. I then give an overview of some own recent formalisms for handling uncertainty and/or vagueness in the Semantic Web.